Preferences of coffee farmers for attributes of selected coffee technologies in the Philippines - Cabral, Jayson S. (Journal of Economics, Management & Agricultural Development, 2022)
This paper looked into the preferences of 151 coffee farmers for the attributes of selected coffee technologies. The study was done to help guide technology developers in crafting post harvest processing facilities for coffee which their target market will need which can lead to a higher probability of commercialization of new coffee technologies. The study examined the preferences for attributes for coffee dryers, moisture meters, coffee depulpers, and coffee sorters using the Analytic Hierarchy Process (AHP) framework. The results revealed that the quality of the final product is the top priority for coffee farmers when choosing a coffee dryer. Non-destructiveness is the most important attribute of coffee moisture meters. The adaptability of the machine to different varieties is the primary concern for coffee depulper. Finally, accuracy is the most important factor when selecting a coffee sorter. Technology innovators should consider the abovementioned attributes in developing coffee technologies to improve their marketability.